Analisis Teknik Penerjemahan Amplifikasi Dalam Novel “L’appel De L’ange” Karya Guillaume Musso - Adjie, Chelsea Senneza; Amalia, Farida; Racmadhany, Ariessa (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
This study is motivated by the importance of translation techniques in preserving the meaning and nuances of literary works. It aims to analyze the use of amplification techniques in the novel L’Appel de l’ange by Guillaume Musso, translated into Indonesian by Yudith Listiandri. The focus is to identify the types of amplification techniques used and analyze their functions within the translated sentences. The study employs a descriptive qualitative method with purposive sampling to select sentences containing amplification techniques. Data were analyzed by categorizing amplification types—explicitation, addition, paraphrase, description, and footnotes—and examining their functions in context. Results show that explicitation is the most frequently used technique (125 sentences), followed by addition (31 sentences), paraphrase (19 sentences), description (18 sentences), and footnotes (6 sentences). These findings highlight the significant role of amplification techniques in influencing the simplicity and complexity of sentence structures in translation.